SEMINAR ON THE USE OF ANTIBIOTIC IN PEDIATRIC PATIENT DIAGNOSIS OF DIARRHEA IN HOSPITAL OF Drs. H. Amri Tambunan - Ratih Anggraeni; Apri Marni Hutapea (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Diarrhea is an infectious disease that can cause mortality in children under five and infants. One of the organisms that can cause diarrhea is bacteria. The bacteria that most often infect humans are Campylobacter bacteria, Salmonella bacteria, and Eschericia coli bacteria. Diarrhea can be characterized by the occurrence of bowel movements that are more fluid than usual with a frequency of more than three times in 24 hours. It is still found in the community that knowledge about the use of antibiotics for diarrhea patients is still minimal. Antibiotics are still often traded freely in pharmacies for conditions of digestive disorders, respiratory problems, and general conditions, so this seminar is very necessary to minimize these conditions. This seminar can provide information both to patients, health workers, and the public about the accuracy of treatment indications, patient accuracy, drug accuracy, dosage accuracy, timeliness of administration and accuracy of the way of administering treatment, which in this case is the use of antibiotics at the Hospital of Drs. H. Amri Tambunan 2022. This seminar was conducted based on retrospective medical record data and then analyzed descriptively using purposive sampling method. The result of this seminar is that the seminar participants understand and understand about the use of antibiotics for diarrhea conditions related to the accuracy of treatment indications, patient accuracy, drug accuracy, dosage accuracy, time of administration accuracy and accuracy of administration of antibiotics.